Metodologia de utilização de um sig como ferramenta no auxilio ao gerenciamento de acidentes de trânsito - Santos, Camila Gabrielle de Araújo (Universidade Federal Rural do Semi-Árido, 2018)
Whether it is territorial or population expansion, it raises concerns about sustainable urban mobility, as it calls attention to the increase in the number of the private vehicle fleet in detriment to the collective and sustainable ones. Therefore, it is the responsibility of the public power to guarantee the right of all citizens, the right to travel safely in transit, whether for leisure or work purposes. In this scenario, the work concerns a case study, the project developed at the Federal Rural Semi-Arid University, entitled GIS Platform for management of traffic accidents in Mossoro. The objective of this study is to describe a new methodology applied to obtain geo-referenced data on the occurrence of traffic accidents, using a database and free GIS software for free data analysis, allowing decision-making by managers. The study was based on collecting information on traffic accidents, creating a georeferenced database for possible analysis after the treatment of the georeferenced data in the QGIS software, and analyzing the results already obtained with the application of this methodology. In this way it was possible to conclude that this methodology is fast and efficient, in obtaining reliable and accessible information in the interpretation of the data reached. This facilitates decision-making by public management in relation to preventive and corrective measures of traffic management.
Monografia
Keywords: Mobilidade urbana; Mossoró; Geoprocessamento; Acidentes; QGIS; Urban mobility; Mossoró; QGIS; Accidents; Geoprocessing; ENGENHARIAS::ENGENHARIA CIVIL